High Expression of ROMO1 Aggravates the Malignancy of Hepatoblastoma. (1st September 2021) - Lv, Jiangfeng; Wu, Yan; Li, Wei; Fan, Huaping
Abstract : Hepatoblastoma (HB) is a kind of tumor that occurs frequently in children and is highly malignant. Here, the function of ROS modulator 1 (ROMO1) was identified in the development of HB. In this study, the mRNA expression of ROMO1 was measured by RT-qPCR. Colony formation assay, MTT assay, and flow cytometric analysis were applied to detect cell viability. The cell migrative and invasive ability was measured by wound healing and transwell assays. Tumor xenografts were performed to examine tumor growth. The results showed that upregulation of ROMO1 was identified in liver hepatocellular carcinoma (LIHC) tissues and predicted poor prognosis in LIHC patients. And ROMO1 expression was also increased in HB tissues and cells. Functionally, ROMO1 knockdown restrained cell viability, migration, and invasion in HB. In addition, knockdown of ROMO1 was found to suppress tumor formation in vivo . In conclusion, upregulation of ROMO1 promotes tumor growth and cell aggressiveness in HB.